Mechanistic insight the visible light driven hydrogen generation by plasmonic Au-Cu alloy mounted on TiO2 @B-doped g-C3N4 heterojunction photocatalyst - Babu, Pradeepta; Dash, Soumya Ranjan; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
Designing of two dimensional surfaces and interfaces with light-active materials has been established as a versatile approach to increase their photocatalytic activity. In the present work, n-type anatase TiO2 coupled with p-type B-doped g-C3N4 nanosheet (BCN) were fabricated and Au-Cu nanoalloy with varying atomic ratio were deposited on the p-n heterojunction. The incorporation of Au-Cu on the interface of the dyad enhances light absorption over broad regime, charge separation, and migration. Au-Cu with 1:1 ratio (with an average particle size of 1.2 nm) loaded p-n hetrojunction (TBCAC-1:1) shows excellent photocurrent enhancement (approximately 4.4-folds) in the cathodic direction as compared to their monometallic plasmonic counterpart. Additionally, the catalyst shows photocurrent at zero biased potential as well as lower onset potential as compared to the other alloy. TBCAC-1:1 photocatalyst could able to produce 2150 mu mol h(-1)g(-1) of hydrogen, which is (approximately 3-folds) as compared to their monometallic counterparts. The hydrogen evolution process for Au-Cu (1:1) system was found to be governed by the charge distribution which dictates the binding preference of the Au and Cu sites leading to the water splitting as investigated by DFT calculation. The excellent hydrogen generation by the photocatalyst links to the synergistic effect between Au and Cu associated with the hot electron photochemistry due to surface plasmon resonance phenomenon. (C) 2022 Published by Elsevier B.V.
Keywords: Doped carbon nitride; hydrogen production; LSPR; P-n junction; Photocatalysis; Plasmonic alloy

Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.